Quest for Behavioural Traces the Neural Way : A Study on BSE 100 along with its Oscillators - Ghosh, Bikramaditya (Indian Journal of Research in Capital Markets, 2017)
S&P BSE 100 is a broad-based index in the Indian capital market. They have many a diverse investor groups investing on a daily basis with contrasting ideas, knowledge bases,Â information inputs, and organic expertise. Presence of cognitive errors or overconfidence in the prediction methodology, heuristic simplification or decisions using mental shortcuts to arrive at quicker but uncertain outcomes, familiarity bias or selecting familiar stuff over more efficient, however, unfamiliar conditions and variables cannot be ruled out. This study, using neural networks on the said index, attempted to identify and determine traces of all the behavioural biases along with the construction of a reasonably accurate prediction model at the same time.